Relationship between self-management behavior and family care among Chinese older adults hospitalized for stroke: the mediating role of chronic disease resource utilization - Wang, Zhangyi; Zhu, Fen; Zuo, Juan; Yang, Li; Lu, Feng; Chen, Li; Li, Liping; Tang, Xiaochun; Wang, Tingrui; Wu, Junbo; Xie, Weimin; Zhan, Yating; et al. (Frontiers in Medicine, 2025)
BackgroundThe importance of self-management behavior has been widely acknowledged in global studies, demonstrating its effectiveness in improving patients’ emotional well-being, enhancing quality of life, preventing stroke recurrence, and reducing mortality and readmission rates. However, existing research indicates that self-management behavior among older adults hospitalized for stroke remains underdeveloped. Furthermore, limited studies have examined the correlations between self-management behavior, family care, and chronic disease resource utilization in this population.ObjectiveThis study aims to investigate self-management behavior, family care, and chronic disease resource utilization among Chinese older adults hospitalized for stroke and to explore the relationships among these variables. Specifically, it examines the mediating role of chronic disease resource utilization between self-management behavior and family care.MethodsA cross-sectional correlational design followed the Strengthening the Reporting of Observational Studies in Epidemiology checklist for quality reporting. Between December 2023 and January 2025, a total of 627 Chinese older adults hospitalized for stroke were recruited from three tertiary grade-A hospitals in two cities in China. Data were collected using the Demographic Characteristics Questionnaire, the Stroke Patient Self-Management Behavior Assessment Scale, the Family APGAR Scale, and the Chronic Illness Resources Survey. Descriptive statistics, univariate analysis, correlation analysis, and process plug-in mediation effect analysis were applied to the data.ResultsThe total scores for self-management behavior, family care, and chronic disease resource utilization were (M = 165.94, SD = 51.26), (M = 5.51, SD = 1.65), and (M = 72.15, SD = 16.73), respectively. These scores indicate moderate levels of self-management behavior, family care, and chronic disease resource utilization. Self-management behavior was positively correlated with family care (r = 0.615, p < 0.01) and chronic disease resource utilization (r = 0.536, p < 0.01). Furthermore, chronic disease resource utilization partially mediated the relationship between self-management behavior and family care, accounting for 41.6% of the total effect.ConclusionThe self-management behavior, family care, and chronic disease resource utilization among Chinese older adults hospitalized for stroke were found to be at moderate levels, indicating a need for improvement. Family care directly affects self-management behavior and indirectly affects it through chronic disease resource utilization. Healthcare professionals should focus on enhancing health education and providing psychological support for stroke patients to improve family care, alleviate fears regarding disease progression, and ultimately promote better self-management behavior.